Análise dos indicadores de manutenção de caminhões fora-de-estrada modelo 930E - ARAGÃO, Romário de Brito (2024)
Preventive maintenance is essential as it improves the physical availability of trucks, reduces downtime, and prolongs their lifespan. This article aims to analyze the maintenance indicators of equipment in a mining company in southeastern Pará. For this purpose, a qualitative analysis of the results of the MTBF, Availability, and MTTR indicators and the loss profile was conducted. It was observed that they delivered an Availability of 73%, above the budgeted figure for the fleet; an MTBF of 29 hours, below the budgeted 39 hours; and an MTTR of 4 hours, within the target of up to 5 hours. It is concluded that despite frequent fluctuations in the indicators, the fleet delivers satisfactory results in its objectives